Zootopia - Howard, Byron; Moore, Rich (Richard); Bush, Jared, 1974-; Spencer, Clark; Goodwin, Ginnifer; Bateman, Jason; Elba, Idris; Slate, Jenny, 1982-; Torrence, Nate, 1977-; Hunt, Bonnie; Lake, Don; Chong, Thomas, 1938-; et al. ([Burbank, California] : [Walt Disney Home Entertainment], 2016)
Zootopia is a city like no other. Comprising habitat neighborhoods like ritzy Sahara Square and frigid Tundratown, it's a melting pot where animals from every environment live together. But when optimistic Officer Judy Hopps arrives, she discovers that being the first bunny on a police force of big, tough animals isn't so easy. Determined to prove herself, she jumps at the opportunity to crack a case, even if it means partnering with a fast-talking, scam-artist fox, Nick Wilde
Story by Byron Howard, Rich Moore, Jared Bush, Jim Reardon, Josie Trinidad, Phil Johnston, and Jennifer Lee
Originally released as a motion picture in 2016
Special features (DVD): Scoretopia; "Try everything" music video (Shakira)
Special features (Blu-ray): Research : a true-life adventure; The origin of an animal tale; Zoology : the roundtables; Scoretopia; Z.P.D. forensic files; "Try everything" music video (Shakira); deleted characters; deleted scenes
Editors, Fabienne Rawley, Jeremy Milton ; music, Michael Giacchino ; visual effects supervisor, Scott Kersavage ; head of animation, Renato Dos Anjos
Voices: Ginnifer Goodwin, Jason Bateman, Idris Elba, Jenny Slate, Nate Torrence, Bonnie Hunt, Don Lake, Tommy Chong, J.K. Simmons, Octavia Spencer, Alan Tudyk, Shakira
Keywords: Animals -- Juvenile films; Police -- Juvenile films; Prejudices -- Juvenile films; Animals; Police; Children's films; Animated films; Feature films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Animated films; Children's films; Feature films; Juvenile works; Video recordings for people with visual disabilities; Video recordings for the hearing impaired